On the understanding of students’ learning and perceptions of technology integration in low- and high-embodied group learning - Ioannou, Marianna; Georgiou, Yiannis; Ioannou, Andri; Johnson-Glenberg, Mina (My University, 2019)
Embodied learning activities supported by motion-based technologies are becoming popular in various contexts and settings. However, little is yet known about technology integration for embodied learning in groups in authentic classroom settings, as existing studies have been mostly conducted in laboratory settings. In this work, we examine students’ learning and perceptions of technology integration for group learning in a high-embodied, Kinect-based educational game (Condition1, n=24 students), in comparison with a low-embodied, desktopbased version of the same game (Condition2, n=18 students), in an authentic classroom setting. Data collection included questionnaires evaluating students’ baseline, knowledge gains, perceptions of technology integration, and post-activity interviews. Findings showed higher learning gains and more positive perceptions of technology integration, in terms of opportunities for student negotiation, for the students in the low-embodied condition. Implications are discussed for supporting high-embodied learning activities for group learning in authentic classroom settings. This work is part of a project that has received funding from the European' s Horizon 2020 research and innovation programme under grant agreement Nº739578 and the government of the Republic of Cyprus through the Directorate General for European Programmes, Coordination and Development.
Keywords: Embodied learning activities; Motion-based technologies; Technology integration; Group learning